Cetuximab combined with paclitaxel or paclitaxel alone for patients with recurrent or metastatic head and neck squamous cell carcinoma progressing after EXTREME. (25th May 2021) - Chevalier, Thomas; Daste, Amaury; Saada‐Bouzid, Esmaa; Loundou, Anderson; Peyraud, Florent; Lambert, Tiphaine; Le Tourneau, Christophe; Peyrade, Frédéric; Dupuis, Charlotte; Alfonsi, Marc; Fayette, Jérôme; Reure, Juliette; et al.
Abstract: BACKGROUND: Prognosis of recurrent or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) remains poor. The addition of cetuximab, to platinum and fluorouracil chemotherapy (EXTREME regimen) has been shown to improve patients' outcomes in first‐line settings. METHODS: We conducted a retrospective, multicenter study, including HNSCC that progressed after a first line of platinum‐based chemotherapy and cetuximab, treated either by paclitaxel + cetuximab (PC) or paclitaxel alone (P), between January 2010 and April 2018. The end points were overall survival (OS), progression‐free survival (PFS), and overall response rates (ORR). Patients were matched according to their propensity scores, estimated with a logistic regression model. The secondary objectives were to study the safety profile and to look for prognostic and predictive factors of effectiveness. RESULTS: Of the 340 identified patients, 262 were included in the analysis, 165 received PC, and 97 received P. In unmatched population, ORR was 16.4% with PC and 6.2% for P. Median PFS was 2.9 months [95% Confidence Interval 2.7–3.0] for PC versus 2.5 months [2.2–2.7] for P, hazard ratio (HR) = 0.770 [0.596–0.996]. Median OS was 5.5 months [4.4–6.9] for PC versus 4.2 months [3.4–4.8] for P, HR = 0.774 [0.590–1.015]. In multivariate analysis, PC was associated with better PFS and OS. These results were consistent in matched‐paired population. Previous cetuximab maintenance for more than 3 months was predictive of better OS with PC. CONCLUSION: Although the continuation of cetuximab in combination with paclitaxel after EXTREME provides moderate benefit, it could be an interesting option for selected patients. Abstract : In this propensity score‐adjusted, multi‐institutional series, cetuximab in association with paclitaxel showed better outcomes than paclitaxel alone for patients who had disease progression after EXTREME regimen, particularly for patients who benefit the most from cetuximab in first‐line setting. This study should raise the question of the place of this association with the arrival of immune checkpoint inhibitors in first line with or without chemotherapy.